2023
DOI: 10.1155/2023/2971065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Syphilis among Mothers with Missed Opportunities for Antenatal Syphilis Testing in Rural Western Uganda: A Cross-Sectional Study

Theoneste Hakizimana,
Joy Muhumuza,
Fabrice Molen Selamo
et al.

Abstract: Background. Early prenatal syphilis testing and treatment are essential preventative measures for maternal syphilis and associated adverse pregnancy outcomes of pregnancy; however, data shows that two-thirds of all cases are missed among women who visit prenatal care center at least once but are not tested for syphilis. This study determined the prevalence and factors associated with syphilis infection among mothers with missed opportunities for antenatal syphilis testing in rural western Uganda delivered at F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The discovered deficiency in knowledge on mother-to-child transmission (79.3%) highlights the significance of antenatal education to decrease the risk of vertical transmission. Study done in Uganda reported poor knowledge of syphilis mode of transmission 52.4% (Hakizimana et al, 2023). The high prevalence of stillbirths (23.3%) necessitates additional research into the possible impact of syphilis on negative pregnancy outcomes and emphasizes the need for timely identification and care.…”
Section: Discussionmentioning
confidence: 99%
“…The discovered deficiency in knowledge on mother-to-child transmission (79.3%) highlights the significance of antenatal education to decrease the risk of vertical transmission. Study done in Uganda reported poor knowledge of syphilis mode of transmission 52.4% (Hakizimana et al, 2023). The high prevalence of stillbirths (23.3%) necessitates additional research into the possible impact of syphilis on negative pregnancy outcomes and emphasizes the need for timely identification and care.…”
Section: Discussionmentioning
confidence: 99%